Vitamin E Extraction from Magnesium Salts of Palm Fatty Acid Distillates - Lestari, Dianika; Aqilah, Khalisa Putri; Putri, Salsafia; Harimawan, Ardiyan; Mudhakir, Diky; Insanu, Muhamad (Journal of Engineering and Technological Sciences, 2022)
This research studied how the type of organic solvent and the number of extraction stages affect the vitamin E cumulative extraction yield and recovery rate from Mg-PFAD. First, PFAD was saponified to produce Mg-PFAD, then vitamin E was extracted from the Mg-PFAD using ethanol, isopropanol, or hexane, followed by evaporation to produce vitamin E concentrate. Three-stage hexane extraction with a solvent to Mg-PFAD mass ratio of 3 kg solvent/kg Mg-PFAD produced the highest vitamin E recovery rate. Organic solvent with a lower polarity gave a higher extraction yield and recovery rate of vitamin E from Mg-PFAD. In general, an increase of the number of extraction stages led to an increase of the vitamin E extraction yield and recovery rate from Mg-PFAD.